2022
DOI: 10.1093/oncolo/oyab073
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Pembrolizumab in Combination with Capecitabine and Oxaliplatin with Molecular Profiling in Patients with Advanced Biliary Tract Carcinoma

Abstract: Background We conducted a phase II study of the combination of pembrolizumab with capecitabine and oxaliplatin (CAPOX) in patients with advanced biliary tract carcinoma (BTC) to assess response rate and clinical efficacy. Exploratory objectives included correlative studies of immune marker expression, tumor evolution, and immune infiltration in response to treatment. Patients and Methods Adult patients with histologically con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…In a phase II study of pembrolizumab plus capecitabine and oxaliplatin (CapOx) for 11 patients with BTC, 8 of patients had received one or more systemic platinum-based chemotherapies. Three patients with GBC were enrolled, 2 of whom were evaluated for SD and 1 for PR ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a phase II study of pembrolizumab plus capecitabine and oxaliplatin (CapOx) for 11 patients with BTC, 8 of patients had received one or more systemic platinum-based chemotherapies. Three patients with GBC were enrolled, 2 of whom were evaluated for SD and 1 for PR ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since radio-chemotherapy-induced DNA damage may activate RLRs signaling and induce an immune response, the combination of radio-chemotherapy with immune checkpoint inhibitors has been evaluated in clinical trials [ 318 , 319 ]. The randomized PACIFIC study demonstrates that treatment of stage III NSCLC patients, who do not have disease progression after platinum-based chemoradiotherapy, with anti-PD-L1 antibody durvalumab improves the overall survival [ 271 ].…”
Section: Clinical Testing Of Cancer Therapy Involving Rlrs Activationmentioning
confidence: 99%
“…Durvalumab is an IgG1 κ monoclonal antibody, which acts as a PD-L1 blocker, can bind to PD-L1 on tumor cells, and block its interaction with PD-1 of T cells and antigen-presenting cells, thereby relieving PD-1/PD-L1-mediated immunouppression, promoting T cell proliferation, and strengthening the immune killing effect on tumors. A controlled trial involving 685 cases showed that Durvalumab combined with GEMCIS significantly prolonged OS compared with GEMCIS 119 , and similar regimens were Camrelizumab combined with GEMOX and Pmbrolizumab combined with CAPOX 120 , 121 . The above studies showed that the combination of PD-L1 blocker and chemotherapeutic drugs had good efficacy in patients with advanced CCA.…”
Section: Current Status Of Immunotherapy For Ccamentioning
confidence: 99%